Emerging role of lipid metabolism alterations in Cancer stem cells - Yi, Mei (J Exp Clin Cancer Res, 2018)
BACKGROUND: Cancer stem cells (CSCs) or tumor-initiating cells (TICs) represent a small population of cancer cells with self-renewal and tumor-initiating properties. Unlike the bulk of tumor cells, CSCs or TICs are refractory to traditional therapy and are responsible for relapse or disease recurrence in cancer patients. Stem cells have distinct metabolic properties compared to differentiated cells, and metabolic rewiring contributes to self-renewal and stemness maintenance in CSCs. MAIN BODY: Recent advances in metabolomic detection, particularly in hyperspectral-stimulated raman scattering microscopy, have expanded our knowledge of the contribution of lipid metabolism to the generation and maintenance of CSCs. Alterations in lipid uptake, de novo lipogenesis, lipid droplets, lipid desaturation, and fatty acid oxidation are all clearly implicated in CSCs regulation. Alterations on lipid metabolism not only satisfies the energy demands and biomass production of CSCs, but also contributes to the activation of several important oncogenic signaling pathways, including Wnt/β-catenin and Hippo/YAP signaling. In this review, we summarize the current progress in this attractive field and describe some recent therapeutic agents specifically targeting CSCs based on their modulation of lipid metabolism. CONCLUSION: Increased reliance on lipid metabolism makes it a promising therapeutic strategy to eliminate CSCs. Targeting key players of fatty acids metabolism shows promising to anti-CSCs and tumor prevention effects.